Quantitative determination of Nebivolol Hydrochloride and Rosuvastatin Calcium in laboratory prepared mixture by robust, high-performance liquid chromatographic method - Sandeep Bolla; Narender Boggula (Discover Chemistry)
Abstract A robust and eco-friendly high-performance liquid chromatographic (HPLC) method has been developed and validated to quantify Nebivolol Hydrochloride and Rosuvastatin Calcium in a laboratory-prepared mixture, following ICH guidelines. Utilizing a Shimpack ODS C18 column with a mobile phase consisting of Methanol, Acetonitrile, and phosphate buffer (pH 3.5, adjusted with ortho-phosphoric acid) in a 40:20:40 (v/v/v) ratio, the method achieved effective separation and detection at 281 nm. The assay demonstrated excellent linearity, precision, and accuracy for both drugs, with retention times of 2.455 min for Nebivolol and 6.197 min for Rosuvastatin. Forced degradation studies under acidic, basic, oxidative, thermal, and photolytic conditions revealed the method’s stability-indicating capability, with distinct separation of degradation products. The method’s environmental impact was assessed using the Analytical Eco Scale, AGREE metrics, and GAPI (Green Analytical Procedure Index), yielding favorable greenness scores (AES: 69, AGREE: 0.61), signifying moderate adherence to green analytical chemistry principles. This validated method is reliable for routine analysis and quality control, making it applicable to pharmaceutical and analytical laboratories.